KONTRIBUSI MOTIVASI MEMASUKI DUNIA KERJA DAN PENGALAMAN PRAKERIN TERHADAP HASIL UKK - A. Fajri Alvi; Efrizon Efrizon (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
This researchwas conducted to find out how much motivation contribution entered the world of work and industrial work practice experience (PRAKERIN) on the results of the Expertise Competency Test (UKK) from Electronics Engineering Students in 2019 at SMK Negeri 1 West Sumatra. The population of this research is as many as 58 students of class XII majoring in electronics engineering (audio video engineering expertise program and mechatronic engineering program) SMK Negeri 1 West Sumatra 2018/2019 academic year. Sampling in this research was carried out by simple random sampling technique, so as to get as many as 37 students as the sample. The questionnaire shared and filled out by these students is a method used by the writer to collect data. Multiple regression analysis is the main analysis technique used in this research. From this research, it was found that (1) Motivation to enter the workforce and industry work experience experience together contributed 30.14% to the results of the expertise competency test, (2) Motivation to enter the workforce contributed 15.05% to expertise competency test results, (3) Industrial work practice experience contributes 14.67% to the results of expertise competency test. So it can be concluded that Motivation entering the workforce and the industrial work practice experience (PRAKERIN) contribute to the results of the Expertise Competency Test (UKK) of Electronics Engineering students in 2019 at SMK Negeri 1 West Sumatra. Keywords:Motivation Entering the Workforce, Industrial Work Practice Experience, Expertise Competency TestKONTRIBUSI MOTIVASI MEMASUKI DUNIA KERJA DAN PENGALAMAN PRAKERIN TERHADAP HASIL UKK